Solid–liquid transitions in Mn-based ionic liquids [MeIM]2[MnBr4] and [EtIM]2[MnBr4] producing emission spectra with narrow green bands. (March 2023) - Shimono, Seiya; Sekine, Masataka; Niwa, Yasuhiro; Sagayama, Hajime; Araki, Koji; Hata, Yoshiaki; Kishimura, Hiroaki
Highlights: Organic–inorganic hybrid materials prepared via conventional solid-state reaction. Crystal structure and magnetic and optical properties of prepared materials studied. [MeIM]2 [MnBr4 ] and [EtIM]2 [MnBr4 ] existed in solid state at room temperature. Luminescence properties caused by phase transitions between solid and liquid states. Luminescence properties also influenced by the [MeIM] + and [EtIM] + cations. Abstract: In this study, novel organic–inorganic hybrid materials, particularly [MeIM]2 [MnBr4 ] and [EtIM]2 [MnBr4 ], were synthesized by a conventional solid-state reaction method and characterized by X-ray diffraction, X-ray absorption fine structure spectroscopy, differential scanning calorimetry, and magnetic and optical measurements. The emission spectra of these compounds exhibited narrow green bands at 529 and 519 nm, respectively, due to the electronic transitions of the 3 d 5 configuration of the Mn 2+ ion. In addition, [EtIM]2 [MnBr4 ] demonstrated a quantum efficiency of 74.5%. According to the X-ray absorption fine structure spectra, differential scanning calorimetry curves, and temperature dependences of the photoluminescence spectra, the luminescence properties of the studied materials were caused by the phase transitions between their solid and liquid states and influenced by the [MeIM] + and [EtIM] + cations. Graphical abstract: Image, graphical abstract